Penerapan Tema Extending Tradition Pada Perancangan Museum Kebudayaan Aceh di Banda Aceh - Araini Magfirah; Dyah Erti Idawati; Muliadi Muliadi (Universitas Syiah Kuala, 2022)
Abstrak Museum kebudayaan merupakan tempat memamerkan benda kebudayaan tradisional suatu daerah. Sebuah museum hendaknya mampu memenuhi fungsi sebagai sarana edukasi dan wisata. Museum Kebudayaan Aceh yang dibangun dimaksudkan dapat menjadi sarana edukasi serta rekreasi dengan memberikan pemahaman dan pejelasan mengenai 8 etnis yang ada di Aceh yaitu Etnis Aceh, Jamee, Singkil, Devayan, Kluet, Gayo, Alas dan Tamiang. Kota Banda Aceh sendiri terdapat museum kebudayaan Aceh, namun belum terdapat penjelasan mendalam terkait 8 etnis di Aceh Serta bangunan museum yang tidak terlalu menarik minat wisatawan sehingga kurangnya jumlah pengunjung pada museum tersebut. Penerapan tema pada sebuah rancangan merupakan sebuah solusi, yaitu mampu mempengaruhi minat wisatawan untuk datang. Penerapan tema Extending Tradition pada Museum Kebudayaan Aceh dengan menggunakan metode 3D Visualization diharapkan dapat memberikan pengalaman mengenal budaya yang lebih realistis dibanding sebelumnya. Pembangunan museum kebudayaan Aceh ini diharapkan dapat menjadi sarana edukasi serta rekreasi dan sebagai wadah mengenalkan beragam kebudayaan 8 Etnis di Aceh kepada masyarakat setempat serta wisatawan. Application of the Extending Tradition Theme in the Design of the Aceh Cultural Museum in Banda AcehAbstract Cultural museum is a place to exhibit traditional cultural objects of an area. A museum should be able to fulfill its function as a means of education and tourism. The Aceh Cultural Museum that was built is intended to be a means of education and recreation by providing an understanding and explanation of the 8 ethnic groups in Aceh, namely the Acehnese, Jamee, Singkil, Devayan, Kluet, Gayo, Alas and Tamiang. The city of Banda Aceh itself has a museum of Acehnese culture, but there is no in-depth explanation regarding the 8 ethnicities in Aceh. And the museum building is not very attractive to tourists, so there is a lack of visitors to the museum. The application of a theme in a design is a solution, which is able to influence the interest of tourists to come. The application of the Extending Tradition theme at the Aceh Cultural Museum using the 3D Visualization method is expected to provide a more realistic cultural experience than before. The construction of the Aceh cultural museum is expected to be a means of education and recreation and as a place to introduce various 8 Ethnic cultures in Aceh to the local community and tourists.